Diseño y desarrollo de un plan de implementación de buenas prácticas de manufacturación (BPM) para la empresa de lácteos “Don Pato”. - Mena Yugcha, Cristian Santiago (2021)
The Don Pato dairy company began in 2003 with the implementation and manufacture of artisanal salt cheeses which were made by the Technologist German Proaño, previously the owner of the dairy company "Don Pato", it is a factory dedicated to the production of a wide range of dairy products and their marketing. The most outstanding problems of the company are due to the lack of food safety that is essential for the preparation and manufacture of food for human consumption. The objective set for this work is the design and development of an implementation plan for Good Manufacturing Practices (GMP) for the dairy company "Don Pato". The procedure and method that was used is the one established in the Sanitary Regulation, Control and Surveillance Agency (ARCSA, 2015-2018) through which the following items were evaluated according to the established norm: facilities, equipment and utensils, compliance with the personnel, raw materials and supplies, production operations, packaging, labeling, transportation, marketing, quality assurance and control. The method used was inductive, since the particularities of the processes carried out in the company were observed and a planning was executed that allowed the implementation of the BPM. Based on this, a planning was executed that allowed the implementation of the BPM. By carrying out the checklist we obtained that the aspects that influenced the production operations were; the non-existence of records, documents to control the production procedures in the production of cheese and yogurt, the lack of periodic validation of procedures for cleaning and disinfection. The most outstanding results were the design and development of a plan (BPM) that will help the company to take corrective measures in the long term and that will guarantee the manufacture of products with high levels of food safety.